From Listening to Healing Music Appreciation Education as a Pathway to College Students’ Emotional Adjustment - Wang, Luting (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
In the context of intense social competition, mental health issues among college students have garnered widespread societal attention. Music appreciation education serves as a vital pathway for mental health and quality education in higher education institutions. Consequently, how to achieve effective emotional adjustment through music appreciation education has become a significant topic in contemporary university mental health. This study deconstructs music appreciation education to construct an emotional adjustment pathway within it. Firstly, the study establishes emotional adjustment as the orientation of music appreciation education. It positions music appreciation content as the foundation for emotional adjustment, the instructional process as the pathway for its implementation, and the evaluation of music appreciation education as the key to emotional adjustment. Secondly, this study designs a four-tier model for emotional adjustment in music appreciation education: emotional perception and recognition, emotional adjustment and experience, psychological adaptation and stress management, and personality development and core competency enhancement. Building upon this, an evaluation system oriented toward emotional adjustment is constructed. This research provides theoretical support and practical pathways for integrating music appreciation education with mental health education in higher education, holding positive significance for promoting the comprehensive development of college students.